1978
DOI: 10.1177/000331977802901007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manual Lymph Drainage Massage on Urinary Excretion of Neurohormones and Minerals in Chronic Lymphedema

Abstract: Treatment of 29 cases of chronic lymphedema of various origins, mostly of the lower limbs, by manual lymph drainage massage resulted in significant changes of neurohormone excretion in the urine, whereas the secretion of 17-KS, thyroxine, minerals, and creatinine was not significantly changed. Comparison of the values of urinalysis before and after manual lymph drainage of the patients showed the following changes: 17-KS; -3.5% (non significant); 17-OH: -31% (significant); adrenaline: +50% (significant); norad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…The role of the lymphatic system is often not fully understood among hand therapists and hand surgeons, although many articles emphasise the necessity of lymphatic drainage of plasma proteins and fluid from the injured area (Casley-Smith 1981, Drake et al 1998, Ikomi et al 1996, Sallustio et al 2000, Szczesny and Olsweski 2002. Fluid transportation both in veins and lymphatics needs skeletal muscle contraction and the lymphatic system has, in addition, its own ability to pump and to increase its capacity several times (Boland and Adams 1999, Boris et al 1994, Campisi et al 2001, Földi and Clodius 1989, Kurz et al 1978, Morey and Watson 1986, Rockson 2001, Sallustio et al 2000, Schmid-Schonbein 1990, Simons et al 1996, Szczesny and Olsweski 2002, 2003. The MLD technique, according to Vodder, used in this study to reduce oedema was applied in the experimental group six times for 40 minutes over 13 days.…”
Section: Control Experimentalmentioning
confidence: 98%
See 1 more Smart Citation
“…The role of the lymphatic system is often not fully understood among hand therapists and hand surgeons, although many articles emphasise the necessity of lymphatic drainage of plasma proteins and fluid from the injured area (Casley-Smith 1981, Drake et al 1998, Ikomi et al 1996, Sallustio et al 2000, Szczesny and Olsweski 2002. Fluid transportation both in veins and lymphatics needs skeletal muscle contraction and the lymphatic system has, in addition, its own ability to pump and to increase its capacity several times (Boland and Adams 1999, Boris et al 1994, Campisi et al 2001, Földi and Clodius 1989, Kurz et al 1978, Morey and Watson 1986, Rockson 2001, Sallustio et al 2000, Schmid-Schonbein 1990, Simons et al 1996, Szczesny and Olsweski 2002, 2003. The MLD technique, according to Vodder, used in this study to reduce oedema was applied in the experimental group six times for 40 minutes over 13 days.…”
Section: Control Experimentalmentioning
confidence: 98%
“…MLD as described by Vodder (Kurz 1994, Kasseroller 1998, Wittlinger and Wittlinger 1996 is a technique that starts with increasing lymphomotoricity proximal to the injury before reaching the injured area. The massage starts at the left supraclavicular space, draining the lymph fluid into the axillary and subclavian veins (Boiselle Howard 2001, Földi and Clodius 1989, Kasseroller 1998, Kurz et al 1978, Rockson 2001. The number of published studies is limited and they are based on oedema of the hand due to traumatic injuries of the upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…Kurz et al 21 found changes in excretion of urinary neurohormones, specifically significant increases in histamine and serotonin, immediately following MLD in patients with lymphedema whereas no changes were found in healthy controls post-MLD. 21,22 In a pilot study, Tan et al.…”
Section: Quantitative Changes After Mldmentioning
confidence: 99%
“…Kurz et al 21 found changes in excretion of urinary neurohormones, specifically significant increases in histamine and serotonin, immediately following MLD in patients with lymphedema whereas no changes were found in healthy controls post-MLD. 21,22 In a pilot study, Tan et al. 23 reported near-infrared fluorescence imaging visualized lymphatic contractility improvements with an increase in both lymph velocity and propulsive frequencies immediately post-MLD for the involved and contralateral limbs in patients with known lymphedema and in both limbs of healthy controls.…”
Section: Quantitative Changes After Mldmentioning
confidence: 99%
“…Beyond its well-known benefits, MLD is able to improve blood microcirculation blood flow, has peripheral analgesic, central sedative, analgesic, vagotonic reaction [38,39,40,41] and improves muscular recovery after physical exercise [42].…”
Section: Manual Lymph Drainagementioning
confidence: 99%